THE INFLUENCE OF THE LEGAL REGIME OF MARTIAL STATES ON LABOR RELATIONS IN UKRAINE - Dyban, Maksym (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to determine the prospects for the development and improvement of procedural legislation in the field of labor law after the termination or cancellation of the legal regime of martial law and to reveal the problem of legal regulation of labor relations during the legal regime of martial law. Research methods: during the research, general scientific and special legal methods of scientific knowledge were used, in particular: system-structural method, observation method, generalization method, methods of analysis and synthesis. Results: it is claimed that the legal regulation of labor relations in the conditions of the legal regime of martial law has certain gaps, which requires additional research by the scientific community with the involvement of state bodies, lawyers and advocates. Discussion: the question of ineffective regulation of labor relations during the period of martial law in Ukraine was raised, ways of solving problematic issues in this sphere of legal relations were proposed.